Potential impacts of specific global warming levels on extreme rainfall events over southern Africa in CORDEX and NEX‐GDDP ensembles. (2nd December 2019) - Abiodun, Babatunde J.; Mogebisa, Tlakale O.; Petja, Brilliant; Abatan, Abayomi A.; Roland, Takong R.
Abstract: This study examines the potential impacts of specific global warming levels (GWLs) on extreme rainfall events in southern Africa and over 12 major cities in the region. We analysed two regional climate simulation datasets: the Coordinated Regional Climate Downscaling Experiment (CORDEX) and the NASA Earth eXchange Global Daily Downscaled Projections (NEX‐GDDP, hereafter referred to as NEX), which used different methods (dynamical and statistical, respectively) in downscaling several global climate model (GCM) simulations from CMIP5. Twenty simulations were used from each dataset. The simulated rainfall indices for the reference period (1971–2000) were compared with eight observation datasets. The projected changes in rainfall indices were examined at four GWLs under the RCP8.5 climate forcing scenario. The projections from the CORDEX and NEX ensembles were compared and the self‐organizing map (SOM) analysis was used to classify the projected changes from the simulations into 12 groups, based on their similarities. There is a good agreement among the eight observation datasets, albeit with some differences. The two simulation datasets (CORDEX and NEX) capture the climatology of rainfall indices over southern Africa and, in some cases, the simulation errors fall within the observation uncertainties. CORDEX and NEX datasets agree on fewer rain days but more intense rainfall events over southern Africa in the future and indicate that the magnitude of these changes increases with the GWLs. They also agree on a future increase in the frequency and intensity of extreme rainfall events north of 20°S and a decrease south of 20°S. However, CORDEX indicates that the rainfall deficit from the fewer rain events may exceed the rainfall surplus from the more intense rain events, but NEX indicates the opposite. In the SOM classification, while some simulations project a decrease in tropical temperate trough (TTT) rainfall, some project an increase, and some indicate an equatorward shift of the TTT rainfall. The simulations project a decrease in annual rainfall over five cities, an intensification of extreme rainfall over five cities and more frequent extreme rainfall events over four cities. The results of this study have application in mitigating the future impacts of extreme rainfall events over southern Africa, especially in the cities. Abstract : The study domain showing the topography of southern Africa and the location of the 12 cities used in the study. The red square (1o x 1o; longitude and latitude) around each city indicates the area used for calculating extreme rainfall over the city.